Exploring the Benefits and Challenges of Social Media in English Language Learning: Insights from English Education Students - Wati, Siska Oktawidya; Budiyanti, Kurnia; Mizkat, Eva; Juita, Novia; Ardi, Havid (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aimed to investigate the potential benefits and challenges associated with using social media in English language learning, focusing on English education students. The research used a mixed-method design, incorporating questionnaires. The benefits of using social media in learning English are multifaceted and significant. English learning also enhances their digital literacy and technology skills. Social media platforms provide learners with access to authentic language use in real-time contexts, allowing them to observe and engage with native speakers, which enhances their understanding of colloquial expressions and cultural nuances. the interactive nature of social media fosters active participation and communication practice, which are crucial for developing speaking and writing skills. Social media also offers diverse content, from educational videos and articles to interactive exercises and language learning communities, catering to various learning preferences and needs. English education students have identified several challenges when using social media for learning English, alongside potential solutions to these issues. Some challenges are perceived more negatively (distractions, language barriers, and material credibility), others are seen in a more positive light (maintaining focus and self-discipline and balancing time). The perception varies across different aspects of learning English on social media, highlighting the complexity of the experience and the individual preferences and challenges of the respondents. It is essential to consider these perceptions when designing educational strategies and support systems for learners on social media platforms.